Rigid-flexible coupling modelling and dynamic performance analysis of novel flexible road wheel. (March 2020) - Deng, Yaoji; Zhao, Youqun; Xu, Han; Lin, Fen; Wang, Qiuwei
A novel flexible road wheel with hub-hinge-ring combined structure is introduced to improve the buffer damping performance and lightweight level of tracked vehicles. To balance computational efficiency and precision, an advanced rigid-flexible coupled model of the flexible road wheel is established using a hybrid modelling method combining finite element method and multi-body dynamics. The reliability and accuracy of the established rigid-flexible coupled model are verified by wheel static loading experiment. The modal flexible body of the elastic outer ring is developed by modified Craig-Bampton method and the simulated results are in good agreement with the experimental data. Based on the verified rigid-flexible coupled model, the dynamic characteristics of the flexible road wheel under typical operation conditions were investigated. The simulation results show that when the motion state changes, the elastic outer ring will produce a hysteretic angle with respect to the hub, delaying the transmission of torque. The system parameters have a greater effect on the vertical vibration of the flexible road wheel. The higher the vehicle speed, the more vibration will be caused, and the increase in the load and number of hinge groups will reduce the vibration. The research results provide reference for structure optimization of flexible road wheel and lay a foundation for flexible multi-body dynamic simulation of tracked vehicles with flexible road wheels.